Pengujian Pasar Efisien dan Single Index Model pada Peristiwa Pengumuman Kenaikkan Harga BBM di Bursa Efek Indonesia - Hidayat, Riskin (Potensio, 2008)
Abstract This study aimed to test the efficiency of capital markets and the Single Index Model in Indonesia, related to the an- nouncement of fuel price rise on May 24, 2008. The sample in this study as many as ten stocks listed on the Indonesia Stock Exchange (IDX) and actively traded on 10 (ten) days before and 10 (ten) days after the announcement of fuel price rise on May 24, 2008, or by a window period of 21 days. The results showed that in the event that the announcement of fuel price increases announced by the government on May 24, 2008 are no differences in average abnormal return of between 10 (ten) days before and 10 (ten) days after the announcement. In periods of negative abnormal return ob- servations occurred before the announcement of fuel price increases, which means there have been leaks of informa- tion, where the issue of fuel price increases have been in- formed by the previous government. This shows that the In- donesian capital market is not efficient in this case. The study also found that the SIM does not apply to the period of obser- vation, because of the variability of the beta is not followed by the variability of stock returns or in other words there is no linear relationship between beta and returnKey Word: Efficiency of capital markets, Single Index Model